2016
DOI: 10.1080/19443994.2015.1021852
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of effluent quality parameters in a submerged membrane bioreactor with simultaneous upward and downward aeration treating municipal wastewater using hybrid models

Abstract: 2015): Modeling of effluent quality parameters in a submerged membrane bioreactor with simultaneous upward and downward aeration treating municipal wastewater using hybrid models, Desalination and Water Treatment, A B S T R A C TThis research was an effort to develop hybrid multilayer perceptron and radial basis function artificial neural network-genetic algorithm (MLPANN-GA and RBFANN-GA) models to accurately predict effluent biochemical oxygen demand (BOD), chemical oxygen demand (COD), total nitrogen (TN), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 37 publications
2
13
0
Order By: Relevance
“…Figure 6 demonstrates that the MLP-NN model predicted the effluent COD, TP, and TSS with high accuracy based on the test data set. The results of our study confirm a high generalisation capability of MLP-NN algorithm, as has been reported in a number of studies (Bagheri et al, 2015;2016b;Mirbagheri et al, 2015). Figure 7 demonstrates the regression lines for the MLP-NN model predicting effluent COD, TP, and TSS based on the train, test, validation, and all data sets.…”
Section: Nn-based Prediction Of Effluent Characteristicssupporting
confidence: 87%
See 1 more Smart Citation
“…Figure 6 demonstrates that the MLP-NN model predicted the effluent COD, TP, and TSS with high accuracy based on the test data set. The results of our study confirm a high generalisation capability of MLP-NN algorithm, as has been reported in a number of studies (Bagheri et al, 2015;2016b;Mirbagheri et al, 2015). Figure 7 demonstrates the regression lines for the MLP-NN model predicting effluent COD, TP, and TSS based on the train, test, validation, and all data sets.…”
Section: Nn-based Prediction Of Effluent Characteristicssupporting
confidence: 87%
“…Artificial intelligence and machine learning techniques have shown high capabilities in various fields of science and engineering (Kavousi and Saadatmand, 2018). Neural networks (NNs) are artificial intelligent models, which have been successfully used for monitoring and predicting various parameters in water and wastewater treatment (Mirbagheri et al, 2015; Bagheri et al, 2016a; 2016b). In recent years, the NNs have been frequently used due to their several advantages over activated sludge models such as parameter estimation and calibration (Bagheri et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…It makes and gives some options for the water reuse process that can be installed and built as needed from the cases. Membrane bioreactors (MBR) is defined as a mechanical system that consists from some any part such as backwash pumps, effluent pumps, timer, pressure gauges, membrane modules, feeding tanks, and some the others [14]. Basically this mechanism was doing some filtration from any molecules or particle that needed to clean up and make the water in better quality.…”
Section: Resultsmentioning
confidence: 99%
“…Since Yamamoto and his colleague proposed the idea of submerging membranes in the bioreactor in 1989, the membrane bioreactor (MBR) has become a technology that competes with conventional activated sludge process. This process has several advantages, such as high organic loading rate, due to the high mix liquor suspended solid concentration (MLSS) in the bioreactor, lower excess sludge production caused by higher sludge retention time (SRT), lower physical footprint owing to shorter hydraulic retention time (HRT), and excellent effluent water quality [1,2,3]. In spite of its reputation as a secure and high operational reliability technology, membrane fouling is still a major problem that hinders the widespread and large-scale applications [4].…”
Section: Introductionmentioning
confidence: 99%